Pengembangan Media Pembelajaran Smart Apps Creator Pada Pembelajaran IPAS Di Kelas V Sekolah Dasar - Sari, Lavenia Permata; Erita, Yeni (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is motivated by the lack of use of technology-based media in the learning process. One of the innovations in technology-based learning media is Smart Apps Creator. Smart Apps Creator. The aim of this research is to determine the validity and practicality of the media developed and produce Smart Apps Creator learning media for science and technology learning in class V. The type of research carried out is development research using the ADDIE development model. The test school in the research was class V SDN 07 Kapau and the research school was class V SDN 14 Gadut. The research results showed that learning media had a material validity level of 90.76%, language validity 95%, media validity 98.33% with a very valid category. Meanwhile, the results of the practicality test at the trial school obtained a percentage of 94.28% in the very practical category for the teacher response questionnaire and 95.11% for the student response questionnaire in the very practical category. Furthermore, the results of the practicality test at the research school were 100% in the very practical category for the teacher response questionnaire and 96.70% in the very practical category for the student response questionnaire. It can be concluded that the Smart Apps Creator learning media for science and science learning in class V elementary school is valid and practical.